2016
DOI: 10.5603/cj.a2016.0010
|View full text |Cite
|
Sign up to set email alerts
|

Should we wait until severe pulmonary hypertension develops? Efficacy of percutaneous mitral balloon valvuloplasty in patients with severe pulmonary hypertension: A subgroup analysis of our experience

Abstract: Background: The primary goal of this study is to evaluate the immediate and long-term effects of percutaneous mitral balloon valvuloplasty (PBMV) on patients with rheumatic mitral stenosis (MS) complicated with severe pulmonary hypertension (PH 47 ± 6.59 mm Hg, p < 0.001, p < 0.001). Systolic pulmonary artery pressure (SPAP) significantly decreased p < 0.001 (Cardiol J 2016; 23, 2: 184-188)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Because of missing data regarding immediate post-procedural sPAP in some cases, we were unable to analyze the impact of this factor separately. However, some studies have shown that patients with high baseline pulmonary arterial pressure had poorer hemodynamic results in intermediate and late follow-up periods [28,29]. Ozkan et al suggested that because of the decrease in hemodynamic response to PTMC in patients with severe pulmonary hypertension in the long-term, it would be reasonable to perform PTMC at earlier stages [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of missing data regarding immediate post-procedural sPAP in some cases, we were unable to analyze the impact of this factor separately. However, some studies have shown that patients with high baseline pulmonary arterial pressure had poorer hemodynamic results in intermediate and late follow-up periods [28,29]. Ozkan et al suggested that because of the decrease in hemodynamic response to PTMC in patients with severe pulmonary hypertension in the long-term, it would be reasonable to perform PTMC at earlier stages [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that patients with high baseline pulmonary arterial pressure had poorer hemodynamic results in intermediate and late follow-up periods [28,29]. Ozkan et al suggested that because of the decrease in hemodynamic response to PTMC in patients with severe pulmonary hypertension in the long-term, it would be reasonable to perform PTMC at earlier stages [28]. In light of our parallel clinical finding, we also hypothesize that patients with high pulmonary arterial pressure, despite the documented substantial initial improvement after PTMC, may have surpassed the window of opportunity for this procedure, making it reasonable to opt directly for surgical management in some of these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatic MS is an important health issue in Asia . Fluoroscopy‐guided balloon valvuloplasty is known to be safe and effective in selected patients with rheumatic mitral stenosis, and its role is well‐established in the literature worldwide . At the beginning of this study, valvuloplasty performed under echocardiography guidance only was introduced to meet the needs of patients in whom radiation and contrast exposure needs to be avoided such as pregnant women, and patients allergic to iodine or with renal dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Fluoroscopy-guided balloon valvuloplasty is known to be safe and effective in selected patients with rheumatic mitral stenosis, and its role is well-established in the literature worldwide. 12 At the beginning of this study, valvuloplasty performed under echocardiography guidance only was introduced to meet the needs of patients in whom radiation and contrast exposure needs to be avoided such as pregnant women, and patients allergic to iodine or with renal dysfunction. [5][6][7] We posited that the latter echocardiography guidance option also should be encouraged for all patients to avoid the detrimental radiation exposure of both doctors and patients, reduce cost, and allow adaptation to an outpatient procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is one of the post-procedural parameters associated with long-term outcome [21]. PMBV may even be, to some extent, effective in patients with severe pulmonary hypertension (systolic PAP > 75 mmHg) [22]. Still, preventive intervention before development of pulmonary hypertension is of utmost importance because the positive effect of PMBV on right ventricular function in the acute period may disappear in the mid-term [23].…”
Section: Impact Of Pmbv On Systolic Papmentioning
confidence: 99%